The cohesion elements in Maqamat Al-Zamakhshari - Mohd Ismath, Nurul Hanilah; Al- Anbar, Abdullah (The University of Jordan, 2018)
The study investigates the Cohesion elements in the “Maqǎmǎt Al- Zamakhshari”. This study aims to highlight the combination between the grammatical, semantics, and rhetoric features in order to understand this “Maqǎmǎt” as well as to indicate the strong relations between the arabic linguistics traditions with the modern linguistic theories from the perspective of textual analysis. The study concludes that Arabic linguistic traditions have many elements of cohesion in the the science of text analysis. The study, in this respect, points out the eligibility of utilising the cohesion elements in “Maqǎmǎt al- Zamakhshari”.